PUBLIC POLICIES FOR SPORTS AND RECREATION FOR YOUTH: THEORETICAL APPROACHES (Fiep Bulletin - online, 2011)
This paper aims to review concepts related to sports, leisure and public policies for youth. We understand youth as a transitional phase of life from childhood to adulthood during which important biological, psychological, social, and cultural changes occur. Sport in the context of young people's leisure activities is one among many ways of expressing a certain lifestyle, always related to choices that groups can make. Thus, public policies for youth should promote and encourage the multiple cultural and artistic dimensions of this population that falls short of demands to meet their needs, reshaping sectoral policies.
Keywords: sports/recreation; youth; public policies